From Comrades to Bodhisattvas Moral Dimensions of Lay Buddhist Practice in Contemporary China - Fisher, Gareth (University of Hawaii Press, 2014)
Moreover, as the later chapters of the book discuss, by writing, copying, and distributing Buddhist-themed materials, the practitioners participate in creating a religious network of fellow-Buddhists across the country, thereby forming a counter-cultural community within contemporary urban China.Highly readable and full of engaging descriptions of the real lives of practicing lay Buddhists in contemporary China, From Comrades to Bodhisattvas will interest specialists in Chinese Buddhism, anthropologists of contemporary Asia, and all scholars interested in the relationship between religion and cultural change